Sources and Determinants of Vitamin D Intake in Danish Pregnant Women - Jensen, Camilla B. (MDPI, 2012)
Vitamin D deficiency during pregnancy has been associated with the development of several adverse health outcomes, e.g., pre-eclampsia, gestational diabetes mellitus, preterm delivery, low birth weight, birth length, and bone mineral content. The aims of the present study were to estimate the intake and sources of vitamin D in Danish pregnant women and to examine potential determinants of vitamin D intake of the recommended level (10 µg per day). In 68,447 Danish pregnant women the mean ± SD for vitamin D intake was 9.23 ± 5.60 µg per day (diet: 3.56 ± 2.05 µg per day, supplements: 5.67 ± 5.20 µg per day). 67.6% of the women reported use of vitamin D supplements but only 36.9% reported use of vitamin D supplements of at least 10 µg. Supplements were the primary source of vitamin D for the two higher quartiles of total vitamin D intake, with diet being the primary source for the two lower quartiles. Determinants of sufficient total vitamin D intake were: high maternal age, nulliparity, non-smoking, and filling out of the Food Frequency Questionnaire (FFQ) during summer or fall. We propose that clinicians encourage vitamin D supplementation among pregnant women, with special focus on vulnerable groups such as the young, smokers and multiparous women, in order to improve maternal and fetal health both during and after pregnancy.